RESEARCH ON RIGIDITY ＆ STRENGTH ANALYSIS OF FRANCIS RUNNER AND IMPROVEMENT MEASURES - ZHAO DaoLi; WANG HuaYou; WU ZiJuan; LIANG WuKe; NAN HaiPeng; GUO PengCheng; SUN WeiPeng (Jixie qiangdu)
For the problem of excessive stresses in the runner after hydraulic turbine reformation,two solutions are put forward in this paper,which are the extension of the outlet edge of the blade near the crown and applying reinforcing triangular piece. In order to identify the loads acting on the runner,the water flow of whole passage has been investigated by using CFD method. The water pressure was loaded on the finite element model of runner,and rigidity ＆ strength analysis was conducted.The maximum equivalent stress and the maximum deformation of runner in two solutions were obtained. The results show that: the maximum stress of the original runner appears in rated condition,because the pressure difference between the pressure side and suction side at the center of blade and outlet of near the crown is very big,thus the distribution of load is uneven. Under the rated condition,the maximum stress of blade decreases by 14. 5% in the same degree in both the two solutions. The maximum total deformation of blade in solution A is greater than which in solution B. The maximum stress is located in the the intersection of triangular piece and blade outlet,which is a little far from the blade root,so the force condition of blade root is improved effectively. At the same time,the flow field analysis results show that energy characteristics and the cavitation performance in the two solutions under various operating conditions is less affected.